Characterising CD8+ T cell transcriptomic and clonal consequences of immune checkpoint blockade for the treatment of cancer - Watson, RA (2023)
Background: Immune checkpoint blockade (ICB) is arguably the greatest advance in medical oncology this century. Nonetheless, responses are highly variable. Mechanistic insights into this heterogeneity promises to improve patient stratification and identification of therapeutic targets.